High temperature ion irradiation effects in MAX phase ceramics. (15th February 2016) - Clark, D.W.; Zinkle, S.J.; Patel, M.K.; Parish, C.M.
Abstract: The family of layered carbides and nitrides known as MAX phase ceramics combine many attractive properties of both ceramics and metals due to their nanolaminate crystal structure and are promising potential candidates for application in future nuclear reactors. This investigation examines the effects of energetic heavy ion (5.8 MeV Ni) irradiations on polycrystalline samples of Ti3 SiC2, Ti3 AlC2, and Ti2 AlC. The irradiation conditions consisted of midrange ion doses between 10 and 30 displacements per atom at temperatures of 400 and 700 °C, conditions relevant to application in future nuclear reactors and a relatively un-explored regime for this new class of materials. Following irradiation, a comprehensive analysis of radiation response properties was compiled using grazing incidence X-ray diffraction (XRD), nanoindentation, scanning electron microcopy (SEM), and transmission electron microscopy (TEM). In all cases, XRD and TEM analyses confirm the materials remain fully crystalline although the intense atomic collisions induce significant damage and disorder into the layered crystalline lattice. X-ray diffraction and nanoindentation show this damage is manifest in anisotropic swelling and hardening at all conditions and in all materials, with the aluminum based MAX phase exhibiting significantly more damage than their silicon counterpart. In all three materials there is little damage dependence on dose, suggesting saturation of radiation damage at levels below 10 displacements per atom, and significantly less retained damage at higher temperatures, suggesting radiation defect annealing. SEM surface analysis showed significant grain boundary cracking and loss of damage tolerance properties in the aluminum-based MAX phase irradiated at 400 °C, but not in the silicon counterpart. TEM analysis of select samples suggest that interstitials are highly mobile while vacancies are immobile and that all three materials are in the so-called point defect swelling regime between 400 and 700 °C. All results are consistent with previous work involving traditional and MAX phase ceramics. Results show the aluminum MAX phases are not fit for application near 400 °C and that the silicon MAX phase is more damage tolerant at 400–700 °C. Graphical abstract: Aluminum MAX phases (Ti3 AlC2, Ti2 AlC) are not fit for application in irradiation environments near 400 °C due to anisotropic swelling that induces cracking, whereas the Ti3 SiC2 MAX phase is overall more damage tolerant at 400–700 °C.